6. DAMPAK PROGRAM PENGEMBANGAN NUKLIR KOREA UTARA TERHADAP HUBUNGAN BILATERALNYA DENGAN TIONGKOK TAHUN 2013 – 2015 - Isnaeni, Nur Afiyah; Utomo, Tri Cahyo; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
China and North Korea have had good bilateral relations, as the result of their geographical proximity and their similar ideology (communist). China’s status as a member of the UN Security Council and its stable economy, causes North Korea to depend on diplomatic and economic support from China. North Korea needs diplomatic support from China because its nuclear proliferation since North Korea decided to withdraw from the non-proliferation treaty. As North Korea’s closest ally, China provided diplomatic support by not fully supporting UN sanctions for North Korea’s first and second nuclear tests. However, China did not provide diplomatic support when North Korea launched the third nuclear test, on the contrary, China supported UN Sanction towards North Korea. This research aims to analyze the causes of China’s policy changes toward North Korea nuclear test. The theoritical framework in this research is the concept of neo-classical realism. The type of this research is descriptive, using qualitative data analysis techniques from literatures review. This research shows that there are two causes of China’s policy changes toward North Korea nuclear test, which are: the international structure (pressure from the United States) and China’s domestic conditions (leader, power, and society).